2020
DOI: 10.1039/d0cp03754k
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of exohedrally doped neutral silicon clusters LnSin (n = 5, 10; Ln = Sm, Eu, Yb)

Abstract: Lanthanide doped silicon clusters have been extensively studied in the fields of optoelectronics, magnetism and nanomaterials during last decade. Herein, the systematic structure searches for typical neutral clusters of lanthanide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Global minimum searches for low-lying structures of Nb 7 C n (n = 1-7) clusters were performed in three steps: Firstly, we employed the SK global search method [30][31][32] combined with DFT calculation to search and optimize the structure. In recent years, our research group has effectively predicted the ground-state structures and electronic properties of binary mixed clusters utilizing the SK-DFT method [33][34][35][36][37][38][39][40][41]. All the atoms are placed at the same point initially and then are "kicked" randomly with a sphere of some radius.…”
Section: Methodsmentioning
confidence: 99%
“…Global minimum searches for low-lying structures of Nb 7 C n (n = 1-7) clusters were performed in three steps: Firstly, we employed the SK global search method [30][31][32] combined with DFT calculation to search and optimize the structure. In recent years, our research group has effectively predicted the ground-state structures and electronic properties of binary mixed clusters utilizing the SK-DFT method [33][34][35][36][37][38][39][40][41]. All the atoms are placed at the same point initially and then are "kicked" randomly with a sphere of some radius.…”
Section: Methodsmentioning
confidence: 99%
“…Two global optimization schemes (SK and ABC) complement each other to obtain the real global optimal structure. Our group has successfully performed the investigations of binary clusters by these methods [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Silicon has drawn considerable attention from the scientific community as an inexpensive and abundant material used in the semiconductor industry. Moreover, it is a prevalent material as building blocks of new tunable nanomaterials whose electronic properties can be controlled by changing the size, shape and composition of the unit clusters. , Considerable research has been carried out in the domain of zintl phases of Si for the synthesis of Si nanoparticles. Reports regarding the isolation of the nine atom Si cluster are recurrent in the literature. , It has also been observed that incorporation of impurity atoms in the Si clusters, TM@Si n , induced suitable property in them while also making them stable. Encapsulation of transition metal in Si clusters instead led to quenching of the magnetic moment of the transition metal atoms due to hybridization effects . In this connection, doping Si clusters externally with two transition metals may lead to high magnetic moment superatomic clusters through magnetic interaction between the two spin centersa ferromagnetic interaction will rationally contribute to high magnetic moment in the cluster.…”
Section: Introductionmentioning
confidence: 99%